Change in Dental Visits among Eligible Children under the Impact of the Child Dental Benefits Schedule in Australia - Lan Nguyen; Luke B. Connelly; Stephen Birch; Ha Trong Nguyen (Global Labor Organization (GLO), 2025)
This study aimed to evaluate the impact of the Child Dental Benefits Schedule (CDBS) on dental visits among eligible children and adolescents in Australia. The study analysed the data set from the birth cohort (B cohort) in the Longitudinal Study of Australian Children (LSAC). A difference-in-differences analysis was used to examine 22,985 observations in the period 2008-2018. The analyses showed that the CDBS policy had a statistically significant and positive impact on dental visits among eligible children and adolescents. There was a 6.1-6.4 percentage point increase (p-value < 0.001) in dental visits across different specifications after the introduction of the CDBS policy. The removal of financial barriers was beneficial to improve dental visits, however, the target group still faces the other remaining barriers, especially those related to inequalities in the social determinants of health, impeding the uptake of free dental services.
Keywords: H43; I14; I18; J13; 330; Dental Care; Government Programs; Children; Adolescents; Longitudinal Studies